ANALISIS RISIKO KEBANGKRUTAN PT SRITEX TBK DENGAN MODEL ALTMAN & GROVER - Paramita, Annisa; Erlina; Ruth, Eugenia; Leksono, Ferosiana; Nofryanti (Jurnal Riset Terapan Akuntansi, 2025)
This study investigates the impact of financial distress on the bankruptcy status of PT Sri Rejeki Isman Tbk (Sritex) using the Altman Z-Score and Grover methods, based on financial statement analysis from 2018 to 2023. Financial distress is a financial condition that serves as an early indicator of potential bankruptcy if not effectively managed. The Altman Z-Score and Grover models are employed as predictive tools to assess bankruptcy risk based on key financial ratios. The analysis results indicate that PT Sritex has shifted from the grey zone to financial distress since 2021, marked by declining liquidity, profitability, and increasing liabilities. The Altman Z-Score method reveals that the company has been in financial distress since 2021, with Z-Scores falling below the critical threshold of 1.81. Meanwhile, the Grover model also suggests a high bankruptcy risk since 2021, with negative scores worsening in subsequent years. This study confirms that both bankruptcy prediction models can serve as early warning tools for management, investors, and stakeholders in identifying potential financial crises. These findings contribute to strategic decision-making to mitigate bankruptcy risks and enhance the company's financial stability. Keywords: Bankruptcy, Altman Z-Score, Grover.